A review on selective dye adsorption by different mechanisms. Issue 6 (December 2022) - Shi, Yawei; Chang, Qian; Zhang, Tongwen; Song, Guobin; Sun, Ya; Ding, Guanghui
Abstract: The selective adsorption of certain dye components from mixed solutions may be desired for potential recovery and reuse. In this review, the recent works in this field have been comprehensively summarized. The dyes investigated in selective adsorption processes have been summarized, and the analysis methods as well as indexes for the evaluation of selective adsorption performances were discussed. After that, the recent works concerning selective adsorption were classified and discussed based on the different separation mechanisms, including charge-dependent separation, size-dependent separation, hydrogen bonding, π-π interaction, proton migration, time-dependent separation, chemical precipitation, and hydrophobic interaction. Furthermore, the impacts of operational and environmental factors including the solution pH, inorganic salts, the initial dye concentration, the adsorption temperature, the adsorption time, and the concentration ratio of dye components on the selective adsorption performances as well as regeneration of the adsorbents were discussed. This review further highlights the current achievements and hurdles for selective dye adsorption process, and also proposes recommendations for future works, including more attention to effects of operational and environmental factors, more theoretical calculations as well as the development of low-cost adsorbents and new separation mechanisms. Graphical Abstract: ga1 Highlights: Recent advances in selective adsorption of dyes were reviewed. The methods and indexes to evaluate adsorption selectivity were summarized. Various separation mechanisms to achieve selective adsorption were discussed. The impacts of different factors on adsorption selectivity were summarized. The challenges and recommendations for future works were proposed.